A new species of hynobiid salamander (Urodela: Hynobiidae: Pseudohynobius) from Southwestern China - Wei, Gang; Xiong, Jian-Li; Hou, Mian; Zeng, Xiao-Mao (Zootaxa, 2009)
A new species of hynobiid salamander, Pseudohynobius jinfo, is described from Mt. Jinfo, Nanchuan County, Chongqing Municipality, southwestern China. The new species is unique in having a longer tail than in the other species of the genus. Other diagnostic characters include 8–9 vomerine teeth on each side, which distinguishes the new species from P. flavomaculatus and P. kuankuoshuiensis, and the presence of small yellow dorsal spots, and the fore and hind limbs merely meeting when adpressed, which distinguish the new species from P. shuichengensis. A species identification key for the genus Pseudohynobius is also provided.